الصيرفة الإسلامية: الأداء والتحديات : دراسة تحليلية للمصرف العراقي الإسلامي للمدة 1993-2003 - د.بشار ذنون محمد الشكرجي; حلا سامي خضير (PROSPECTIVE RESEARCHES, 2023)
The Islamic banks have made great achievements represented by their international widespread presence. These banks follow the Islamic shariat. However, these banks have met a number of challenges. In Iraq, Islamic banks have emerged in the early nineties of the twentieth century represented by the Islamic Iraqi bank. This bank has started its work under great difficulties and challenges which are a reflection of the volatile environment in which it works. The study tackles this issue in two sections: firstly, the theoretical background of the study and, secondly the study takes the Islamic Iraqi bank as a case study performance which reflects the bank's inability to achieve a satisfactory monetary performance. All this is reflected in the main finding of the study which has proved the hypothesis.